On the validity of summative entrustment decisions. (3rd July 2021) - Touchie, Claire; Kinnear, Benjamin; Schumacher, Daniel; Caretta-Weyer, Holly; Hamstra, Stanley J.; Hart, Danielle; Gruppen, Larry; Ross, Shelley; Warm, Eric; ten Cate, Olle; ,
Abstract: Health care revolves around trust. Patients are often in a position that gives them no other choice than to trust the people taking care of them. Educational programs thus have the responsibility to develop physicians who can be trusted to deliver safe and effective care, ultimately making a final decision to entrust trainees to graduate to unsupervised practice. Such entrustment decisions deserve to be scrutinized for their validity. This end-of-training entrustment decision is arguably the most important one, although earlier entrustment decisions, for smaller units of professional practice, should also be scrutinized for their validity. Validity of entrustment decisions implies a defensible argument that can be analyzed in components that together support the decision. According to Kane, building a validity argument is a process designed to support inferences of scoring, generalization across observations, extrapolation to new instances, and implications of the decision. A lack of validity can be caused by inadequate evidence in terms of, according to Messick, content, response process, internal structure (coherence) and relationship to other variables, and in misinterpreted consequences. These two leading frameworks (Kane and Messick) in educational and psychological testing can be well applied to summative entrustment decision-making. The authors elaborate the types of questions that need to be answered to arrive at defensible, well-argued summative decisions regarding performance to provide a grounding for high-quality safe patient care.